Valued experiences of graduate students in their role as educators in undergraduate training in Ugandan medical schools - Zari Rukundo, Godfrey; Kasozi, Jannat; Burani, Aluonzi; Byona, Wycliff; Kirimuhuzya, Claude; Kiguli, Sarah (BMC medical education, 2017)
In most medical schools, graduate students, sometimes referred to as graduate teaching assistants, often participate in the training of undergraduate students. In developing countries like Uganda, are typically involved in undergraduate training. However, prior to this study there were no standard guidelines for this involvement. At the same time, the views and experiences of the graduate students in their role as educators had not been documented. Therefore, the aim of this study was to explore the views and experiences of graduate students about their involvement in undergraduate training in three Ugandan medical schools. The findings of this study will contribute to the development of policies for training in Ugandan medical schools.
Keywords: Graduate students; Undergraduate training; Medical schools; Uganda